2005
DOI: 10.1042/bj20040655
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the increase in cardiolipin biosynthesis and resynthesis in hepatocytes during rat liver regeneration

Abstract: CL (cardiolipin) is a major mitochondrial membrane phospholipid important for the regulation of mitochondrial function. We examined CL de novo biosynthesis and its resynthesis in isolated rat liver hepatocytes prepared 48 h subsequent to two-thirds PHx (partial hepatectomy). The pool size of CL and its de novo biosynthesis from [1,3-(3)H]glycerol were increased 3.3-fold (P<0.05) and 3.1-fold (P<0.05) respectively in hepatocytes prepared from PHx rats compared with sham-operated controls. The reason for the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These changes in lipid content resemble the results of Cascianelli et al [57], who showed an increased sphingomyelin and cholesterol content in nuclear microdomains of regenerated hepatocytes. Interestingly, increased hepatic cardiolipin synthesis, which is presumed to be under the control of transcription factors that regulate mitochondrial biogenesis [58], as well as the pool size of cardiolipin, increased during liver regeneration [59]. Although this study cannot explore the precise mechanisms of the effects observed, our results suggest that the changes in lipid content in the LM and nuclear fractions may be associated with an increase in the trophoblast proliferation rate.…”
Section: Mitochondria Is a Target Organelle Of Pesticide Toxicity Asmentioning
confidence: 70%
“…These changes in lipid content resemble the results of Cascianelli et al [57], who showed an increased sphingomyelin and cholesterol content in nuclear microdomains of regenerated hepatocytes. Interestingly, increased hepatic cardiolipin synthesis, which is presumed to be under the control of transcription factors that regulate mitochondrial biogenesis [58], as well as the pool size of cardiolipin, increased during liver regeneration [59]. Although this study cannot explore the precise mechanisms of the effects observed, our results suggest that the changes in lipid content in the LM and nuclear fractions may be associated with an increase in the trophoblast proliferation rate.…”
Section: Mitochondria Is a Target Organelle Of Pesticide Toxicity Asmentioning
confidence: 70%
“…33 Our analysis identified that among the proteins down-regulated in AH was a subset involved in the synthesis of cardiolipin (CL) (Table 2), a phospholipid that maintains mitochondria bioenergetics 34 during hepatocyte proliferation and liver regeneration. 35 Figure 7A summarizes the CL biosynthesis pathway and shows the primarily negative correlation between MELD score and enzymes in this pathway, including critical proteins 1acylglycerol-3-phosphate O-acyltransferase 2 (PLCB), protein tyrosine phosphatase mitochondrial 1 (PTPMT1), and hydroxyacyl-CoA dehydrogenase trifunctional complex subunit alpha (ECHA). 36 PLCB and PTPMT1 expression was slightly elevated from AH1 to AH2 but declined from AH2 to AH3 (PLCB being significant), whereas ECHA significantly declined from AH1 to AH3 (Figure 7B).…”
Section: Compromised Hepatic Cardiolipin Biosynthesis In Ac and Ahmentioning
confidence: 99%
“…Subcellular fractions were prepared as previously described [18,21] from murine liver, epidermal fat pad, or RAW 264.7 cells incubated plus or minus LPS. Cells were harvested using PBS and pipetted into test tubes.…”
Section: Preparation Of Subcellular Fractions and Assay Of Enzyme Actmentioning
confidence: 99%